Bacterial Outer Membrane Vesicles Induce Vitronectin Release Into the Bronchoalveolar Space Conferring Protection From Complement-Mediated Killing - Paulsson, Magnus; Che, Karlhans F.; Ahl, Jonas; Tham, Johan; Sandblad, Linda; Smith, Margaretha E.; Qvarfordt, Ingemar; Su, Yu-Ching; Lindén, Anders; Riesbeck, Kristian (Frontiers in Microbiology, 2018)
Pathogens causing pneumonia utilize the complement regulator vitronectin to evade complement-mediated killing. Although vitronectin is associated with several chronic lung diseases, the role of bronchoalveolar vitronectin in pneumonia has not been studied. This study sought to reveal the involvement of vitronectin in the bronchoalveolar space during pneumonia, to assess the effect of outer membrane vesicles and endotoxin on vitronectin release, and to determine whether bacterial pathogens utilize pulmonary vitronectin for evasion. Vitronectin was analyzed in cell-free bronchoalveolar lavage fluid harvested from patients with pneumonia (n = 8) and from healthy volunteers after subsegmental endotoxin instillation (n = 13). Vitronectin binding by Pseudomonas aeruginosa and Haemophilus influenzae was analyzed, and subsequent complement evasion was assessed by serum challenge. The effects of outer membrane vesicles on vitronectin production in mouse lungs and human type II alveolar epithelial cells (A549) were determined. We detected increased vitronectin concentrations in lavage fluid during pneumonia (p = 0.0063) and after bronchial endotoxin challenge (p = 0.016). The capture of vitronectin by bacteria significantly reduced complement-mediated lysis. Following challenge with vesicles, vitronectin was detected in mouse bronchoalveolar space, and mouse alveolar epithelial cells in vivo as well as A549 cells in vitro contained increased levels of vitronectin. Taken together, outer membrane vesicles and endotoxin from Gram-negative bacteria induce vitronectin, which is released into the bronchoalveolar space, and used for evasion of complement-mediated clearance.